(untitled) - Ó Riain, S. (New York, 2004)
his book argues, however, that the state played a central role in developing the Celtic Tiger economy as well, and particularly, the increasingly important Irish high tech industry. Typically seen as an example of successful market-led globalization, high tech growth in Ireland has actually been promoted by a new form of state intervention in the economy--one that fosters local networks of support through decentralized state institutions drawing on extensive local, national and global resources
Keywords: Information technology,Economic development,Economic development,Technological innovations,Computer software industry,Công nghệ thông tin,Phát triển kinh tế,Công nghệ mới,Công nghệ phần mềm máy tính; Economic aspects,Social aspects,Social aspects,Government policy,Khía cạnh kinh tế,Khía cạnh xã hội,Chính sách của chính phủ; Ireland,Ireland,Ireland,Ireland,Ireland,Ireland,Ireland,Ireland